2017
DOI: 10.1515/bpasts-2017-0092
|View full text |Cite
|
Sign up to set email alerts
|

Iterative sliding mode observer for sensorless control of five-phase permanent magnet synchronous motor

Abstract: Abstract. Due to the star connection of the windings, the impact of the third harmonic which does not exist in three-phase permanent magnet synchronous motor (PMSM) cannot be ignored in five-phase PMSM. So the conventional sensorless control methods for three-phase PMSM cannot be applied for five-phase PMSM directly. To achieve the sensorless control for five-phase PMSM, an iterative sliding mode observer (ISMO) is proposed with the consideration of the third harmonic impact. First, a sliding mode observer (SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 32 publications
(58 reference statements)
0
24
0
Order By: Relevance
“…This error is close to zero during the steady state operation and with very small increase at the instants of load torque change. In fact, the estimation error is significantly decreased compared to the results presented in [3], [29] and [39]. Thus, the proposed MRAS-SM observer offers precise estimation and high dynamics response.…”
Section: A Load Torque Variationmentioning
confidence: 74%
See 2 more Smart Citations
“…This error is close to zero during the steady state operation and with very small increase at the instants of load torque change. In fact, the estimation error is significantly decreased compared to the results presented in [3], [29] and [39]. Thus, the proposed MRAS-SM observer offers precise estimation and high dynamics response.…”
Section: A Load Torque Variationmentioning
confidence: 74%
“…It is found that the rotational speed and the estimated one follow the reference speed even at lower speeds. The estimation error is reduced from 6% to 0.2% compared to the work presented in [17]- [20], [26], [29], [39], [43], [44] and [45] as shown in Fig. 20.…”
Section: B Robustness Testmentioning
confidence: 83%
See 1 more Smart Citation
“…In the literature we can find several methods which propose the sensorless control of permanent magnet synchronous machines (PMSM) [2]. These methods are based mostly on the observers, such as Model Reference Adaptive System (MRAS) [3], Extended Kalman Filter (EKF) [4], Luenberger Observer (LO) [5] and Sliding Mode Observer (SMO) [6]. Among these methods, SMO will be chosen to achieve the sensorless control of the seven-phase PMSM due to its simple implementation compared to EKF, which requires an important computation time especially in the case of multiphase machines.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, SMO will be chosen to achieve the sensorless control of the seven-phase PMSM due to its simple implementation compared to EKF, which requires an important computation time especially in the case of multiphase machines. Furthermore, in terms of robustness, the SMO presents a robust structure against the variations of machine parameters and noise compared to the MRAS and LO [6].…”
Section: Introductionmentioning
confidence: 99%